Multivariable pid control tuning based on optimization technique for wastewater treatment plant [electronic resource] - Nur Asmiza Selamat, 1986- (2013)
Thesis (Sarjana Kejuruteraan (Elektrik - Mekatronik dan Kawalan Automatik)) - Universiti Teknologi Malaysia, 2013